Pengaruh Keamanan Informasi dan Perkembangan Teknologi di Era Revolusi 4.0 Terhadap Kinerja Perusahaan (Literature Review Manajemen Kinerja) - Adawiyyah, Robiatul; Fauzi, Achmad; Indriyanah, Anah; safitri, Aulia; Putri Nabila, Elma; Maidani, Maidani; Nurul Izati A, Silvia (Green Publisher, 2023)
In today's technological developments, information security is associated with technical advances in the era of Revolution 4.0 and its impact on companies is an interesting topic. This study aims to find out how technological developments in the era of the Industrial Revolution 4.0 affect Information Security and its Impact on Company Performance. Quantitative methods are considered suitable for this study. Based on the results of research, information security has a positive effect on company performance. In addition, technological developments in the era of the industrial revolution 4.0 have a significant effect on company performance. Information security is an effort that aims to ensure and ensure business continuity by safeguarding information from various threats that may occur which aims to minimize risk and maximize every business opportunity that exists.